Assessment of the Cytotoxic, Antioxidant, and Antimelanogenic Properties of the Extracts of the Orchid Dendrobium - Phuangbubpha, Pornwipa; Deesubin, Patthicha; Saetan, Puretat; Maksup, Sarunyaporn; Obsuwan, Kullanart (Trends in Sciences, 2026)
Dendrobium extracts are rich sources of bioactive phytochemicals with potential applications in cosmetics and healthcare. This study investigated the phytochemical composition and bioactivities of four hybrid cut-flower Dendrobium cultivars: Sonia ‘Jo Daeng’, Suree Peach, Black Pearl, and White Pearl. The crude flower extracts were evaluated for their antioxidant and antimelanogenic properties, and cytotoxic effects against human fibroblasts, keratinocytes, melanocytes, and macrophages. Among the tested cultivars, Black Pearl flower extracts exhibited the highest contents of phenolics, flavonoids, tannins, sugars, and vitamin C, which correlated with strong DPPH and Ferric Reducing Antioxidant Power (FRAP) antioxidant activities. The extracts were noncytotoxic at concentrations ≤ 800 µg/mL, maintaining > 90% cell viability. The extracts of D. Black Pearl and D. Sonia ‘Jo Daeng’ flowers significantly reduced ROS generation in THP-1-derived macrophages. However, Black Pearl extracts decreased melanin production in α-MSH-stimulated B16F10 melanocytes by ~41.0%, comparable to control. These findings suggest Black Pearl as a promising source of natural antioxidants and antimelanogenic compounds suitable for cosmetic and dermatological applications. HIGHLIGHTS Methanolic extracts from flowers of four commercial hybrid Dendrobium cultivars were evaluated for phytochemical contents and skin-relevant bioactivities. Black Pearl exhibited the highest levels of phenolics, flavonoids, tannins, and anthocyanins, and demonstrated the strongest antioxidant capacity (DPPH and FRAP assays). All extracts were non-cytotoxic to fibroblasts, keratinocytes, melanocytes, and macrophage-like cells at concentrations ≤ 800 µg/mL (> 90% viability). Black Pearl reduced intracellular ROS in activated macrophages, supporting antioxidant effects under inflammatory oxidative conditions. Black Pearl suppressed α-MSH-induced melanogenesis in B16F10 cells comparable to kojic acid, emphasizing major experimental outcomes and their potential relevance for cosmetic and dermatological applications. GRAPHICAL ABSTRACT